Northwest History. Forest Fires (Cont'd). (1937)
Kaniksu Forest Not All Doused: Heavy Rains Did Not Cover Entire Area-Fires Are Controlled. Kaniksu Forest Not All Doused: Heavy Rains Did Not Cover Entire Area-Fires Are Controlled. SANDPOINT. Idaho, July 14.— (Special.)—Only parts of the Kaniksu national forest received the beneficial rains Tuesday, Supervisor James E. Ryan reports. The Washington side of the forest, in Pend Oreille county north of Newport, did not receive rain, he said. Two lightning fires were started by thunder storms in the Bismark district, north and west of Bonners Ferry, and another in the Beaver creek district, north of Priest lake, but all were put out before they spread. The Tuesday rain fell heavily in Sandpoint, through the valley to Bonners Ferry, and in scattered areas of Bonner and Boundary counties. Farmers report the downpour was beneficial to the second alfalfa crop, just getting started.